1970
DOI: 10.1136/bmj.2.5702.131
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Graft in Man after Conditioning by Antilymphocytic Serum

Abstract: Summary: Aliogeneic bone marrow grafts carried out after previous administration of antilymphocytic serum alone were attempted in 16 patients. Of these, six had acute myeloblastic leukaemia, four acute lymphoblastic leukaemia, and one a blast cell crisis in polycythaemia vera. Ten of these patients were in an overt phase of the disease and resistant to chemotherapy, while nine had complete agranulocytosis. In five of these patients erythrocyte and leucocyte antigenic markers demonstrated the establishment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
54
0
4

Year Published

1972
1972
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(60 citation statements)
references
References 10 publications
2
54
0
4
Order By: Relevance
“…Autologous recovery of hematopoiesis in patients who failed to engraft after conditioning and stem cell transplantation, as well as responsiveness of patients to immunosuppressive therapies, 1 provided evidence of the pivotal role of the immune system in the disease pathophysiology. Treatment strategy is based on severity of the disease, patient age and availability of an HLA-identical related donor.…”
Section: Introductionmentioning
confidence: 99%
“…Autologous recovery of hematopoiesis in patients who failed to engraft after conditioning and stem cell transplantation, as well as responsiveness of patients to immunosuppressive therapies, 1 provided evidence of the pivotal role of the immune system in the disease pathophysiology. Treatment strategy is based on severity of the disease, patient age and availability of an HLA-identical related donor.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the unexpected improvement of hematopoietic function in some aplastic anemia (AA) patients failing engraftment after bone marrow transplantation 1 led to the systematic application of immunosuppressive therapies, with the majority of the patients now showing hematologic recovery without transplantation. [2][3][4] Many laboratory data has been accumulated to support an immunologic mechanism in idiopathic AA.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Several studies have confirmed immunosuppressive therapy (IST) with antithymocyte globulin (ATG) and cyclosporine (CyA) as a promising therapeutic option for patients lacking HLA-identical related donors. [4][5][6][7][8] Although several potential markers of IST response that appear to reflect the immune pathophysiology of aplastic anemia have been suggested, mainly from adult studies, [9][10][11] none have been widely accepted.…”
Section: Introductionmentioning
confidence: 99%